Recent insights into hematopoiesis in crustaceans - Man-jun Liu (Elsevier, 2021)
Hematopoiesis refers to the phenomenon that hematopoietic stem cells (HSCs) continuously form and produce blood cells with multiple functions. In crustacean, the hematopoietic process produces a variety of hemocytes that form the core and basis of cellular and humoral immunity, which is crucial for crustacean to maintain their lives and protect themselves against microbial infection. The expression of many factors, in the form of transcription factors and humoral factors, are altered during hematopoiesis, which are involved in the regulation of hematopoiesis. Meanwhile, there are also factors that, although not directly involved in the HSCs differentiation or hemocytes production and release, play an essential role in maintaining cellular homeostasis. In this review, we summarize current knowledge on the hematopoietic lineage of crustacean, with a particular focus on the molecular regulation of hematopoiesis, including transcriptional regulation, humoral factors involved in the differentiation of HSCs and the maintenance of hematopoietic homeostasis, which contributes to a systematic understanding of the crustacean hematopoiesis.